(untitled) (Medicine Today, 2013)
Bacteremia and infectious sequelea are frequent complications after sclerotherapy. As cirrhotic patients are immune deficient, bacteremia occurring as a consequence of endoscopic variceal ligation (EVL) may develop systemic infection. The aim of the study was to see the incidence of bacteremia in cirrhotic patients after EVL. In this study 91 cirrhotic patients with grade II-III oesophageal varices were enrolled and 100 EVL sessions were done. Patients receiving antibiotics, having evidence of infection were excluded. After the completion of EVL, blood samples for culture and sensitivity were collected at 5minute and after 30minute and subculture done in Blood Agar and MacConkey Agar media. We followed the patients for a week. Of the one hundred cases there were 30 subjects in Child A, 48 in Child B and 13 in Child C class. Four patients (4%) had positive blood culture after EVL, three of Child A class and one of Child B class and non in Child C class. All three patients of Child A had culture positive in their 30minute sample and not in 5 minute sample. The Child B patient had culture positive in his 5minute sample and not in 30minute sample. The bacterium isolated was Coagulase negative Staphylococcus, which we considered it as contaminant. None of these patients developed any infectious sequelea. The incidence of bacteremia after EVL is yet to be ascertained. Post EVL antibiotic prophylaxis is not recommended. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14109 Medicine TODAY Vol.24(1) 2012 pp.20-22